Do we need to routinely perform cavity shaving with breast-conserving surgery for breast cancer? A systematic review and meta-analysis. (March 2021) - Mohamedahmed, Ali Yasen Y; Zaman, Shafquat; Srinivasan, Ananth; Peterknecht, Elizabeth; Saeed S Mohammed, Salma; AlBendary, Mohamed; Alnzaer, Alsmwal Alnour; Elsamani, Kareemaldin
Abstract: Aims: To evaluate comparative outcomes of breast-conserving surgery (BCS) of breast cancer with and without cavity shaving. Methods: A systematic search of multiple electronic data sources was conducted, and all randomised controlled trials (RCTs) comparing BCS with or without cavity shaving for breast cancer were included. Positive margin rate, second operation rate, operative time, post-operative haematoma, cosmetic appearance and budget cost were the evaluated outcome parameters for the meta-analysis. Results: Six RCTs reporting a total number of 971 patients; 495 of these underwent BCS plus shaving (BCS + S), and 473 underwent BCS alone were included. BCS + S showed significantly lower positive margin rate (Risk Ratio [RR] 0.40, P = 0.00001) and second operation rate (RR 0.38, P = 0.00001). BCS + S demonstrated longer operative time than BCS (79 ± 4 min vs 67 ± 3 min, Mean Difference 12.14, P = 0.002), and there was no significant difference in the risk of post-operative haematoma (RR 0.33, P = 0.20). Conclusion: BCS + S is superior to BCS in terms of positive margins rate and second operation rate. Operative time is longer when cavity shaving is performed. Highlights: A meta-analysis and systematic review comparing breast-conserving surgery with or without cavity shaving. Cavity shaving is associated with lower positive margin rate and subsequently the need for a second operation. Cavity shaving has longer operative time when compared with non-shaving breast-conserving surgery.